Conservation Challenges for Macrognathus acuelatus: A Case Study of Threatened Fish in Bengawan Solo and Brantas Rivers, East Java - Nida'an Khofiyyah; Akhmad Taufiq Mukti; Laksmi Sulmartiwi (Airlangga University, 2024)
Macrognathus aculeatus is a local fish from the Bengawan Solo and Brantas Rivers threatened with extinction. Due to the lack of literacy on the biology of this fish. Biological parameters can be used to determine the condition of this fish in nature. Field observations at five stations from the two rivers were conducted to obtain samples. Biological and reproductive parameters such as weight and length, gonad maturity level (GML), Gonadosomatic Index (GSI), Hepatosomatic Index (HSI), and Condition Factor (CF) were the parameters observed in this study. All data obtained were presented as mean and standard deviation. Furthermore, analysis of variance was conducted using ANOVA (p < 0.05) to determine differences in samples from each observation station. The results showed that some biological factors had significant results (p < 0.05) on Gonadosomatic Index and Hepatosomatic Index). However, there was no significant difference (p > 0.05) in the condition factor. On the other hand, there were significant differences (p < 0.05) in body weight, total length, ovary weight, and fecundity parameters across all sampling sites.